Analysis of reproduction conditions for native ichthiopopulations in the Styr-Horyn hydroecological corridor on the territory of the Western Polissiya of Ukraine - V. Sondak; O. Volkochovets; M. Simon; O. Polishchuk (Ribogospodarsʹka Nauka Ukraïni, 2024)
Purpose. To investigate the state of reproduction conditions, current and in dynamics since 1922, for native ichthyopopulations (NI) of the Styr-Horyn Hydroecological Corridor (HEC) on the territory of the Western Polissiya of Ukraine.